2020
DOI: 10.1093/jscr/rjaa177
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected diagnosis of paediatric subcutaneous sacrococcygeal extraspinal ependymoma: lessons learnt and review of the literature

Abstract: Abstract This case describes a 9-year-old male who presented to general surgical clinic with a 3-year history of persistent natal cleft swelling, previously unsuccessfully treated as a pilonidal abscess in the community with multiple courses of antibiotics. In clinic, a 50 × 30-mm soft tissue swelling was found in the natal cleft and a clinical diagnosis of a pilonidal cyst was made. A cream-coloured solid mass measuring 50 × 35 × 30 mm was subsequently excised u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In our literature review, we found 38 studies that described 78 unique cases of myxopapillary ependymoma occurring in the sacrococcygeal region without extension into the CNS [ Table 1 ]. These were comprised of 35 case reports involving 1 or 2 patients,[ 1 , 3 , 4 , 6 - 14 , 17 - 19 , 21 - 26 , 28 , 31 , 33 - 35 , 38 - 41 , 43 , 45 , 47 , 48 , 50 ] and 3 case series involving 3–32 patients. [ 5 , 20 , 42 ] There were no comparative trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our literature review, we found 38 studies that described 78 unique cases of myxopapillary ependymoma occurring in the sacrococcygeal region without extension into the CNS [ Table 1 ]. These were comprised of 35 case reports involving 1 or 2 patients,[ 1 , 3 , 4 , 6 - 14 , 17 - 19 , 21 - 26 , 28 , 31 , 33 - 35 , 38 - 41 , 43 , 45 , 47 , 48 , 50 ] and 3 case series involving 3–32 patients. [ 5 , 20 , 42 ] There were no comparative trials.…”
Section: Discussionmentioning
confidence: 99%
“…also reported extra CNS lesions that invaded the sacrum and caused left lower extremity pain, weakness, and dermatomal paresthesias in one case, and progressive weakness in bilateral lower extremities with bowel and bladder incontinence in the other. [ 11 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a century ago, Mallory et al first described the case of an ependymoma that developed in the subcutaneous tissue of the sacrococcygeal region [ 9 ]. Since then, only a few cases have been reported in literature with less than 50 reported cases occurring in childhood during the last 35 years ( Table 1 ) [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. They occur more frequently in the sacrococcygeal region, followed by the pelvic region, while cases of onset in the liver, lung, or mediastinum are rarer and mainly described in adulthood [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cases we have described also presented with a mass without associated symptoms, and the initial presumptive diagnosis were epidermoid cyst and germ cell tumor, respectively. In fact, given their localization and the propensity to drain which could suggest a diagnosis of pilonidal cyst or other benign tumors, misdiagnosis at onset is very common, occurring in virtually all cases described in the literature [ 5 , 28 , 34 , 44 ]. Thus, with any soft tissue lesion of the sacrococcygeal region, the differential diagnosis must include also ependymoma, in addition to sacrococcygeal teratoma, neurogenic tumor, soft tissue sarcoma, and metastatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%